2014
DOI: 10.1111/andr.274
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of the risk factors, comorbidities, and consequences of hypogonadism in men

Abstract: SUMMARYThe objective of this review was to summarize the literature on the risk factors, comorbidities, and consequences of male hypogonadism, which is defined as a syndrome complex that includes biochemical confirmation of low testosterone (T) and the consistent symptoms and signs associated with low T. A systematic literature search was performed in PubMed/MEDLINE, EMBASE, Cochrane Library for articles published in the last 10 years on risk factors, comorbidities, and consequences of male hypogonadism. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 68 publications
6
100
1
6
Order By: Relevance
“…Based on current EAU criteria, LOH was present in 13.7 and 15.2% of mRCC and loRCC patients, respectively. Although several epidemiologic studies have been published within the last years, prevalence rates of LOH vary significantly depending on the definitions used for the diagnosis 'hypogonadism' [17] . Despite the recognition that androgen deficiency in men should be defined according to biochemical and clinical criteria, most prevalence rates are based on low testosterone levels alone.…”
Section: Discussionmentioning
confidence: 99%
“…Based on current EAU criteria, LOH was present in 13.7 and 15.2% of mRCC and loRCC patients, respectively. Although several epidemiologic studies have been published within the last years, prevalence rates of LOH vary significantly depending on the definitions used for the diagnosis 'hypogonadism' [17] . Despite the recognition that androgen deficiency in men should be defined according to biochemical and clinical criteria, most prevalence rates are based on low testosterone levels alone.…”
Section: Discussionmentioning
confidence: 99%
“…[241][242][243][244] In male individuals, low testosterone levels are also strongly associated with an increased risk of developing type 2 diabetes mellitus. 245 However, few studies have examined metabolic risk specifically in patients with CHH. Interestingly, even short-term hypogonadism (such as that resulting from discontinuation of sex steroids for 2 weeks) induces increased fasting insulin concentrations in young men with CHH, 246 which suggests that adherence to treatment is also important for promoting metabolic health.…”
Section: Reducing Long-term Health Effects Of Chhmentioning
confidence: 99%
“…Multiple epidemiological studies showed that low testosterone was found in 30–50% of men with T2DM [6] and might predict the future development of T2DM. The causative relationship between low testosterone and T2DM, which was interrelated with advanced age, obesity, metabolic syndrome and other factors, might be bidirectional or multidirectional [10, 22, 23]. In previous studies, obesity was not only strongly associated with diabetes but also inversely related with the blood testosterone levels in men [24].…”
Section: Discussionmentioning
confidence: 99%